2022
DOI: 10.1186/s12891-022-05692-0
|View full text |Cite
|
Sign up to set email alerts
|

Age- and sex-dependent differences in the morphology and composition of paraspinal muscles between subjects with and without lumbar degenerative diseases

Abstract: Background The quality of the paraspinal muscles has been recommended as a surrogate marker for the evaluation of the severity of the lumbar degenerative diseases (LDD). The purpose of this study is to determine the age- and sex-dependent differences in the morphology and composition of the paraspinal muscles between LDD and asymptomatic subjects. Methods We analyzed data from 370 patients and 327 asymptomatic volunteers aged between 18–85 years. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
3
5
0
Order By: Relevance
“…It has been found that the CSA of paraspinal muscles decreases with age [ 32 , 33 ], this is similar to the results in our study that we found a very weak negative correlation between age and CSA of MF and ES at the L5/S1 level. In addition to the influence of age on paraspinal muscles CSA, the present studies also confirmed that age also affects paraspinal muscles fat infiltration [ 32 , 34 ], which is similar to our results. We also found a low to moderate positive correlation between BMI and most paraspinal muscles’ CSA,…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It has been found that the CSA of paraspinal muscles decreases with age [ 32 , 33 ], this is similar to the results in our study that we found a very weak negative correlation between age and CSA of MF and ES at the L5/S1 level. In addition to the influence of age on paraspinal muscles CSA, the present studies also confirmed that age also affects paraspinal muscles fat infiltration [ 32 , 34 ], which is similar to our results. We also found a low to moderate positive correlation between BMI and most paraspinal muscles’ CSA,…”
Section: Discussionsupporting
confidence: 93%
“…We did not find a relationship between the COD and paraspinal PDFF, which may be due to the large span of the course of the disease in this study and the lack of detailed records of patients’ low back pain, whether it was persistent or intermittent. Finally, through multi-factor regression, we found that age and gender also had an impact on the PDFF of paraspinal muscles, which was similar to the results of Huang Y and Huang R et al [ 12 , 32 ]. Of course, in order to exclude the influence of potential factors on paraspinal muscles’ PDFF, we also excluded patients with chronic diseases such as diabetes.…”
Section: Discussionsupporting
confidence: 89%
“…29 Huang et al found that reduced CSA of the multifidus is correlated with LBP, 17 while Huang et al believed that paraspinal area reduction is not a risk factor. 30 In the present study, MRI-measured CSA of the multifidus had a positive correlation at L4-5 and the area of the erector showed a negative correlation at L5-S1, which also confirmed that the erector functions in a compensatory manner in accordance with Huang et al 17 Both CT and MRI can be used for qualitative and quantitative analyses of the paraspinal muscles and have good reliability. However, there are differences between the various studies.…”
Section: Discussionsupporting
confidence: 87%
“…In a previous study [69] it was shown that muscle atrophy and fat infiltration are more pronounced in patients with sLSS than in healthy controls. Further, fat infiltration of the lumbar paraspinal muscles is significantly and positively associated with the severity of lumbar degenerative disease [70]. A recent retrospective study [28] of 165 patients investigated the association between fat infiltration of paraspinal muscle, sagittal spinopelvic alignment, and stenosis severity in patients with degenerative LSS.…”
Section: Plos Onementioning
confidence: 99%